Fuel-Saving Postcapture Detumbling by Dual-Arm Space Robot - Qing Zhou; Xiao-Feng Liu; Yuan-Qing Liu; Guo-Ping Cai; Feng Xu (International Journal of Aerospace Engineering)
After the dual-arm space robot captures a noncooperative target, a closed-chain multibody system is formed, making dynamic modeling and detumbling trajectory planning particularly challenging. This paper proposes a novel trajectory planning strategy that guides the combined system into a uniaxial rotational state about its maximum principal inertia axis. Unlike prior work that focuses solely on eliminating the target’s relative motion, our approach additionally drives the closed-chain system into a dynamically favorable uniaxial rotation. This configuration avoids multiaxis coupling and simplifies subsequent stabilization, requiring only unidirectional thruster torque. By reducing the number of required control directions and eliminating complex angular momentum interactions, the subsequent attitude stabilization becomes more fuel-efficient. As a result, the fuel required for postdetumbling control can be significantly reduced. The detumbling process is executed solely by actuating the joints of the dual manipulators without consuming any base thruster fuel. Numerical simulations validate that the proposed strategy effectively establishes the desired rotational mode and that the joint-space tracking controller enables accurate execution of the planned trajectory.